2021
DOI: 10.1186/s40850-021-00067-9
|View full text |Cite
|
Sign up to set email alerts
|

The neotypification of Frontonia vernalis (Ehrenberg, 1833) Ehrenberg, 1838 and the description of Frontonia paravernalis sp. nov. trigger a critical revision of frontoniid systematics

Abstract: Background Among Oligohymenophorea (Ciliophora, Alveolata) the subclass Peniculia stands as one of the most well-known groups. Frontonia is the largest genus of Peniculia, and its representatives are spread in any type of water bodies as well as in soil. At a first glance, Frontonia species exhibit an overall similar morphology, and form a well-recognizable taxon of ciliates. Despite the general morphological homogeneity, the phylogenetic analysis based on the 18S rDNA sequencing showed that Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 51 publications
(103 reference statements)
1
10
0
Order By: Relevance
“…The polyphyly of Frontonia was recognized in 2007 by Andreoli et al [55,56]. Since then, several studies on the molecular phylogeny of this genus have confirmed this finding [10,17,25,41,54,57]. Our phylogenetic trees also show the polyphyly of Frontonia, as members of Frontonia are separated into three phylogenetically distinct groups (Fig.…”
Section: Phylogeny Of Frontoniasupporting
confidence: 82%
See 3 more Smart Citations
“…The polyphyly of Frontonia was recognized in 2007 by Andreoli et al [55,56]. Since then, several studies on the molecular phylogeny of this genus have confirmed this finding [10,17,25,41,54,57]. Our phylogenetic trees also show the polyphyly of Frontonia, as members of Frontonia are separated into three phylogenetically distinct groups (Fig.…”
Section: Phylogeny Of Frontoniasupporting
confidence: 82%
“…nov. MW243109 differs from its nine most closely related Frontonia sequences by 17-151 nucleotides, with the sequence identity ranging from 90.8% to 98.9 % (Table 2). The two most closely related sequences are F. atra MT040844 and F. minuta MT040846, both of which were submitted by Serra et al [17]. However, they differ from the F. apoacuminata sequence by 17 and 18 nucleotides, respectively, which corresponds to a sequence identity of 98.9 % (Fig.…”
Section: Ssu Rrna Gene Sequence Data and Phylogenetic Analysesmentioning
confidence: 89%
See 2 more Smart Citations
“…Moreover, an attempt was also made for understanding the influence of oxygen concentration level on ciliate community in the specific WWTP condition by separately collecting samples from the nitrification tank (which is regarded as an oxic environment) and the denitrification tank (which is considered to be an anoxic environment). Finally, among the various retrieved ciliate species, Bakuella subtropica was redescribed based on the recently proposed taxonomic standard approach, i.e., the next generation taxonomy (NGTax) (Serra et al, 2020), and a critical revision of the genus was conducted, in line with previous papers from our group (e.g., Serra et al, 2021a;Serra et al, 2021b),with a proposal of some taxa synonymization.…”
Section: Introductionmentioning
confidence: 99%